2003
DOI: 10.1016/s0165-0327(02)00146-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of depression in the postpartum period: a longitudinal follow-up study in high-risk and low-risk women

Abstract: Women at high risk and low risk for depression during the early postpartum period can be detected during pregnancy. High-risk women were only at particular risk during the first 3 months postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 34 publications
11
45
1
2
Order By: Relevance
“…Although PRs for Phase 6 mothers with ‡ 1 stressor were higher than PRs for Phase 5 mothers, among the grouped stressors the PRs were similar and have overlapping confidence intervals. Mothers with a history of mental health conditions are at an increased risk of developing PDS, 14,[48][49][50] and such a history may increase the risk of stressful life events, meeting our criteria for a potential confounding variable. Beginning with Phase 6, MA-PRAMS asked about mother's prior mental health using the question, ''Did you visit a health care worker to be checked or treated for depression or anxiety?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PRs for Phase 6 mothers with ‡ 1 stressor were higher than PRs for Phase 5 mothers, among the grouped stressors the PRs were similar and have overlapping confidence intervals. Mothers with a history of mental health conditions are at an increased risk of developing PDS, 14,[48][49][50] and such a history may increase the risk of stressful life events, meeting our criteria for a potential confounding variable. Beginning with Phase 6, MA-PRAMS asked about mother's prior mental health using the question, ''Did you visit a health care worker to be checked or treated for depression or anxiety?…”
Section: Resultsmentioning
confidence: 99%
“…1,[7][8][9][10][11] Depressive symptoms occur in 10%-15% of women of reproductive age in the United States. 12,13 Although a history of major depressive episodes and other severe psychiatric illnesses such as psychosis are known risk factors for PDS, 1,[14][15][16] 25%-75% of women who experience PDS do not report a psychiatric history. 1,15 Catastrophic perinatal events, such as trauma, 14,17,18 terrorist attack, 19 natural and man-made disasters (e.g., earthquakes, tsunamis, Chernobyl) [20][21][22][23] are predictors of PDS for mothers in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain variables have been associated to alterations of the mother's mood, it has been suggested that high risk pregnancies, obstetric complications or prematureness all contribute to the development of depressive symptoms (Agoub, Moussaoui, and Battas, 2005;Davis, Edwards, Mohay, and Wollin, 2003;Korja et al, 2008;Piyasil and Pichaiyut, 2011;Verdoux, Sutter, Glatigny-Dallay, and Minisini, 2002;Verkerk, Pop, Van Son, and Van Heck, 2003;Vigod, Villegas, Dennis, and Ross, 2010). In births that produce neonatal complications (foetal suffering or hospitalization of the new-born) there is an increase of depressive symptoms (Blom et al, 2010).…”
Section: Socio-demographic and Clinical Variables And Postnatal Deprementioning
confidence: 99%
“…The presence of depressive symptoms during pregnancy has been associated with the onset of depression after childbirth (Chaudron et al, 2001;Milgrom et al, 2008;Saisto, Salmela-Aro, Nurmi, and Halmesmaki, 2001). Some studies have focused on how antenatal depression is a factor that, independently from other variables, can predict the appearance of postnatal depressive symptoms (Kim, Hur, Kim, Oh, and Shin, 2008;Verkerk et al, 2003).…”
Section: Emotional Elements Personality and Postnatal Depressionmentioning
confidence: 99%